Eksistensi Alat Bukti Formal Dalam Perselisihan HubunganIndustrial - Hasan Al Munir; Asri Wijayanti (Wijayakusuma Law Review, 2020)
Formal evidence in industrial relations disputes is very important in fact the parties (workers) are unable toprovide sufficient formal evidence during the process of resolving industrial relations. The purpose of thisresearch found out the substance of legal subjects and legal objects of formal evidence in the process of resolvingindustrial relations disputes. This legal research was a normative juridical with a statute approach. The resultsshowed the substance of formal evidence in industrial relations disputes, consisting of the substance of the legalsubject and the legal object of the evidence. formal evidence in disputes over industrial relations was veryimportant to achieve truth. The resulting recommendations were that special arrangements that needed to bemade to require employers / laborers to provide evidence of industrial relations they carried out.